Associations of the triglyceride-glucose index and remnant cholesterol levels with the prevalence of Carotid Plaque in patients with type 2 diabetes: a retrospective study - Xin Xu; Tianrong Pan; Xing Zhong; Yijun Du; Deyuan Zhang (Lipids in Health and Disease)
Abstract Background The triglyceride-glucose (TyG) index has been identified as an alternative biomarker for insulin resistance (IR), while residual cholesterol (RC) is a simple, cost-effective, and easily detectable lipid metabolite. However, the associations of these two markers with carotid plaque presence remain unclear. Thus, this study aimed to explore their associations with carotid plaque presence. Methods Participants were chosen from patients with T2DM admitted to The Second Affiliated Hospital of Anhui Medical University from October 2023 to April 2024, and they were separated into two groups (patients without carotid plaque and patients with carotid plaque) based on their carotid ultrasound results. By comparing the general information and biochemical indicators of the two groups, we employed multivariate logistic regression models and RCS regression models to investigate the associations of the TyG index and RC levels with carotid plaque presence, and made adjustments based on multiple confounding factors to identify the differences between subgroups. Results This study comprised 278 patients with T2DM in total, including 165 males and 113 females. A multivariate logistic regression study indicated that, after adjusting statistically significant variables screened in LASSO regression, TyG index [OR (95% CI): 1.810 (1.077, 3.113)] and RC [OR (95% CI): 1.988 (1.034, 3.950)] remained the risk factors for carotid plaque presence. According to restricted cubic splines (RCS), RC levels increased linearly with carotid plaque presence (P - nonlinear > 0.05). Conversely, the TyG index and carotid plaque presence did not associate linearly (P - nonlinear < 0.05). Results of subgroup analyses showed no grouping variables exhibited association with TyG index or RC (p for interaction > 0.05). Conclusions In patients with T2DM, both TyG index and RC levels were strongly linked to carotid plaque presence, and could serve as independent risk factors for this presence. Monitoring the TyG index and RC levels can help gain a better understanding and knowledge of carotid plaque presence in patients with T2DM, offering guidance for the clinical prevention and treatment of cardiovascular and cerebrovascular diseases (CCVDs) in patients with T2DM.